2016
DOI: 10.1149/2.1111606jes
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Li+Inventory Losses in LiCoO2/Graphite Cells Using Raman Microscopy

Abstract: The contribution from loss of Li + inventory to capacity fade is described for slow rates (C/10) and long-term cycling (up to 80 cycles). It was found through electrochemical testing and ex-situ Raman analysis that at these slow rates, the entirety of capacity loss up to 80 cycles can be explained by loss of Li + inventory in the cell. The Raman spectrum of LiCoO 2 is sensitive to the state of lithiation and can therefore be leveraged to quantify the state of lithiation for individual particles. With these Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…This figure shows a sudden downshift of the Raman peak wavenumber that must be due to a quick modification of the whole structure. It means that the change of the structure during Li deinsertion is sudden and not progressive as reported in previous studies . One explanation could be that the Li removing drives to an increase of the stress that is suddenly relaxed by a change of the structure.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…This figure shows a sudden downshift of the Raman peak wavenumber that must be due to a quick modification of the whole structure. It means that the change of the structure during Li deinsertion is sudden and not progressive as reported in previous studies . One explanation could be that the Li removing drives to an increase of the stress that is suddenly relaxed by a change of the structure.…”
Section: Resultssupporting
confidence: 54%
“…These bands have been attributed to oxygen vibrations involving mainly O─Co─O bending (E g ) and Co─O stretching (A 1g ) vibrations. Raman downshift of the two bands is observed when x is decreased . For the cubic spinel phase (LT) LiCoO 2 , four bands are observed at around 450, 485, 591, and 607 cm −1 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This shifts the capacity balancing of anode to cathode towards values >1 with respect to the reversible capacity. A capacity ratio of anode/cathode >1 allows a complete (de-)lithiation of the cathode and avoids safety-critical dendrite formation and lithium plating [18][19][20][21].…”
Section: Sample Ageing and Cell Preparationmentioning
confidence: 99%
“…Thinner films could protect the electrodes from HF corrosion. But when the film thickness increases, the resistance to the migration of Li-ions increases [19,20]. Studies [21][22][23][24][25] demonstrated that during charging/discharge cycling, the growth of SEI film increases the impedance of the batteries.…”
Section: Introductionmentioning
confidence: 99%